2011
DOI: 10.1007/s00381-011-1426-9
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic cerebral infarction due to progressive occlusion of the internal carotid artery after minor head injury in childhood: a case report

Abstract: Minor head injury can cause cerebral infarction in childhood, although this is rare. If conservative therapy cannot prevent progressive cerebral infarction, STA-MCA bypass should be considered in case of the ICA occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The larger the area of cerebral infarction is, the more active coagulation function and fibrinolytic system are and the higher the levels of D-dimer and NT-pro BNP is. 19 , 20 This study found that the levels of D-dimer and NT-pro BNP of the patients with massive cerebral infarction were obviously higher than those of the patients in the control group, indicating that patients with severer cerebral infarction had higher levels of D-dimer and NT-pro BNP. It was also found that the levels of D-dimer and NT-pro BNP of the death patients were much higher than those who survived after half-year follow up.…”
Section: Discussionmentioning
confidence: 70%
“…The larger the area of cerebral infarction is, the more active coagulation function and fibrinolytic system are and the higher the levels of D-dimer and NT-pro BNP is. 19 , 20 This study found that the levels of D-dimer and NT-pro BNP of the patients with massive cerebral infarction were obviously higher than those of the patients in the control group, indicating that patients with severer cerebral infarction had higher levels of D-dimer and NT-pro BNP. It was also found that the levels of D-dimer and NT-pro BNP of the death patients were much higher than those who survived after half-year follow up.…”
Section: Discussionmentioning
confidence: 70%
“…However, efficacy of urgent STA-MCA bypass has been reporte [ 6 8 ]. We have performed urgent STA-MCA bypass in patients with progressing stroke owing to occlusion of internal carotid artery or MCA based on our own experiences [ 9 ]. In this case, we selected urgent STA-MCA bypass because the patient presented progressing stroke in spite of aggressive medication.…”
Section: Discussionmentioning
confidence: 99%
“…Neurologic examination isn't only important for neurologist but also for all specialists including anesthesiologist. [13][14][15][16] We suggest that our patient died to ARDS and MCA infarction itself which resulted from hypotension and ischemia. In conclusion, we aimed to emphasize importance of early, detailed neurologic examination for early recognition of MCA infarction.…”
Section: Discussionmentioning
confidence: 99%